Canada Labour Relations Board - Policies and Procedure - Verge, Pierre (Relations Industrielles / Industrial Relations, 1986)
This article reviews the book, "Canada Labour Relations Board - Policies and Procedure," by C.H. Foisy, D.E. Lavery, and L. Martineau.